Antimicrobial and Cytotoxic Activities of Endophytic Fungi Isolated from Artemisia annua L - Puji Astuti, Wahyono, Titik Nuryastuti, Indah Purwantini, Purwanto (Journal of Applied Pharmaceutical Science, 2014)
This study was aimed to investigate antimicrobial and cytotoxic effects of endophytic fungi isolated from A. annua L. The ethyl acetate extracts were obtained by liquid-liquid partition of fermentation broth of endophytes followed by evaporation. Antimicrobial assay was determined by disc diffusion method. Cytotoxicty assay was conducted against T47D, WiDr and Vero using MTT assay. Data generated were used to determine IC50. While DP2 extract did not show any inhibition against all tested bacteria, DP6 extract at 200 µg inhibited the growth of B. subtilis, P. aeruginosa and S. thypi with the highest inhibition against B. subtilis. Similarly, E2 extract inhibited the growth of B. subtilis, E. coli and S. thypi, with the highest inhibition against B. subtilis. The three extracts (DP2, DP6 and E2) were found to be cytotoxic against T47D and WiDr with E2 extract to be the most cytotoxic. These compounds were more selective against T47D cell line with IC50 of 91.7, 74.8 and 12.0 µg/mL, respectively. The IC50 against Vero cell line are 444.4, 140.3 and 87.7 µg/mL, respectively.
Keywords: Antimicrobial, cytotoxic, fungal endophytes, A. annua.